Lifestyle Factors and Bowel Preparation for Screening Colonoscopy - Hyun, Jong Hee; Kim, Sang Jin; Park, Jung Hun; Wie, Gyung Ah; Kim, Jeong-seon; Han, Kyung Su; Kim, Byung Chang; Hong, Chang Won; Sohn, Dae Kyung (Annals of Coloproctology, 2018)
The quality of bowel preparation is a major determinant of the quality of colonoscopy. This study evaluated lifestyle factors, including usual dietary style, associated with bowel preparation. This retrospective study evaluated 1,079 consecutive subjects who underwent complete colonoscopy from December 2012 to April 2014 at National Cancer Center of Korea. Questionnaires on bowel preparation were completed by the subjects, with the quality of bowel preparation categorized as optimal (excellent or good) or suboptimal (fair, poor or inadequate). Lifestyle factors associated with bowel preparation were analyzed. The 1,079 subjects included 680 male (63.0%) and 399 female patietns (37.0%), with a mean age of 49.6 ± 8.32 years. Bowel preparation was categorized as optimal in 657 subjects (60.9%) and as suboptimal in 422 (39.1%). Univariate analyses showed no differences between groups in lifestyle factors, such as regular exercise, alcohol intake, smoking, and dietary factor. Body mass index (BMI) > 25 kg/m2 was the only factor associated with suboptimal bowel preparation on both the univariate (P = 0.007) and the multivariate (odds ratio, 1.437; 95% confidence interval, 1.104-1.871; P = 0.007) analyses. Most lifestyle factors, including dietary patterns, exercise, alcohol intake and smoking, were not associated with suboptimal bowel preparation in Koreans. However, BMI > 25 kg/m2 was independently associated with suboptimal bowel preparation. More intense preparation regimens before colonoscopy can be helpful in subjects with BMI > 25 kg/m2.